Investigating the mechanism of transcriptional regulation of the gonadotropin-releasing hormone receptor (GnRHR) gene by dexamethasone - Von Boetticher, S. (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Biochemistry))--Stellenbosch University, 2008.